(untitled) (Biological Sciences - PJSIR, 2001)
A number of binuclear metal complexes of the type [ML(HP2]2X2 where I-lL = 1-hydrox -2,3-diphenyl-6- amino -6- mercapto -1,4,5 - triaza - 1,3 - hexadiene, M = Co(ll), Ni(ll) and Cu(ll), X = Cl, Br, N03 CI04 have been synthesized and characterized by elemental analyses, magnetic susceptibility, infrared and electronic spectral data.